How to adapt a Traditional LIS Education Curricula to New Needs of Knowledge Organisation: example of the Course "Library Classification and Classification Systems&#34 - Lasić-Lazić, Jadranka; Slavić, Aida (1998)
When defining the course curricula in the department of Information Sciences in Zagreb, we tried to present library classification as the concept of a universally understood indexing language with reference to values that should be used in the future. The reasons why and how LIS education should be changes in the context of an information society are discussed. The main idea and principles on which the course Classification and Classification Systems have been based are also presented here. The choice of methods and procedures used within these tutorials has been illustrated with examples. This is an example of how traditional LIS courses could be adapted to new requirements, with a little more effort and modest technical support. More importantly, the way we are developing our course is an example of how to change the syllabus to make LIS education more pro-active and to prepare future librarians for the knowledge society.
Projekt MZOS
ENG